2017
DOI: 10.2131/jts.42.43
|View full text |Cite
|
Sign up to set email alerts
|

Pathway of 3-MCPD-induced apoptosis in human embryonic kidney cells

Abstract: -3-Chloropropane-1,2-diol (3-MCPD) is a heat-produced contaminant formed during the preparation of soy sauce worldwide. The present investigation was conducted to determine the molecular aspects of 3-MCPD toxicity on human embryonic kidney cells (HEK293). Cell viability and apoptosis were assessed in response to exposure to 3-MCPD using the MTT assay and high-content screening (HCS). DNA damage, intracellular reactive oxygen species (ROS) and apoptosis-related proteins were evaluated. Genes related with apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 39 publications
1
4
1
Order By: Relevance
“…Two reasons can be presented for this phenomena: (1) the decrease in the dissolution of 3‐MCPD in higher doses (0.5 to 10 mM) in the cell culture medium, which led to unwanted reactions with its components, and (2) saturation of the reaction pathway of the metabolite, inhibition of metabolism pathway, and reduction in the resulting substances that have toxic properties. Despite the similarity of the results of this study and other studies conducted on the evaluation of 3‐MCPD cytotoxicity in HEK‐293 cell line and leydig cell, dose‐dependent toxicity pattern was not seen in this study (Ji et al., 2017; Peng et al., 2016; Sun et al., 2013).…”
Section: Resultscontrasting
confidence: 72%
“…Two reasons can be presented for this phenomena: (1) the decrease in the dissolution of 3‐MCPD in higher doses (0.5 to 10 mM) in the cell culture medium, which led to unwanted reactions with its components, and (2) saturation of the reaction pathway of the metabolite, inhibition of metabolism pathway, and reduction in the resulting substances that have toxic properties. Despite the similarity of the results of this study and other studies conducted on the evaluation of 3‐MCPD cytotoxicity in HEK‐293 cell line and leydig cell, dose‐dependent toxicity pattern was not seen in this study (Ji et al., 2017; Peng et al., 2016; Sun et al., 2013).…”
Section: Resultscontrasting
confidence: 72%
“…In addition, the oxidative stress event may cause the induction of mitochondrial cytochrome C which triggered by the ROS (Ji et al, 2017). Our results also supported by Mossoba et al (2020) who reported that HK-2 cells that were treated with 3-MCPD and its esters have shown slightly increased in ROS levels with the increasing concentrations of the treatment.…”
Section: Discussionsupporting
confidence: 91%
“…The cytotoxicity of 3-MCPD has been widely reported in different systems (21,(37)(38)(39). For example, 3-MCPD has been reported to trigger the death of 293 cells via the death receptor and the mitochondrial pathway (37).…”
Section: Fundingmentioning
confidence: 99%
“…The cytotoxicity of 3-MCPD has been widely reported in different systems (21,(37)(38)(39). For example, 3-MCPD has been reported to trigger the death of 293 cells via the death receptor and the mitochondrial pathway (37). Furthermore, 3-MCPD has been reported to induce apoptosis in rat brain cells via activation of caspase 3 (38).…”
Section: Fundingmentioning
confidence: 99%